2019
DOI: 10.1002/jccs.201900200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring beta amyloid cleavage enzyme‐1 inhibition and neuroprotective role of benzimidazole analogues as anti‐alzheimer agents

Abstract: Beta amyloid cleavage enzyme-1 (BACE1) is the key enzyme involved in Aβ peptide formation in Alzheimer's disease pathogenesis. We intend to target this enzyme by exploring benzimidazole analogues against BACE1 as potential anti-Alzheimer agents. Docking studies were performed to determine the hydrogen bond interactions between the designed molecules and the target protein's active site. Research indicates the relationship between oxidative stress and Aβ effect in precipitating neurodegeneration; hence, the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…4 Furthermore, many benzimidazoles are screened for their potential anti-inflammatory, 5 antiviral 6 antiproliferative, and anthelmintic properties. 7 Likely, these compounds exhibited potent free radical scavenging properties as demonstrated in several reports, 8,9 which can be attributed to neuroprotection in Parkinson's, 10 Alzheimer's, 11 and other memory impairment models. 12,13 In this context, the beneficial effects of benzimidazole against multiple neurodegenerative's targets have been recently reviewed.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…4 Furthermore, many benzimidazoles are screened for their potential anti-inflammatory, 5 antiviral 6 antiproliferative, and anthelmintic properties. 7 Likely, these compounds exhibited potent free radical scavenging properties as demonstrated in several reports, 8,9 which can be attributed to neuroprotection in Parkinson's, 10 Alzheimer's, 11 and other memory impairment models. 12,13 In this context, the beneficial effects of benzimidazole against multiple neurodegenerative's targets have been recently reviewed.…”
Section: Introductionmentioning
confidence: 70%
“…Several studies reported benzimidazole derivatives' antioxidant and anti-inflammatory activities. 11,12,[45][46][47][48][49] GSH and GST are essential endogenous antioxidants that help to eliminate free radicals. Benzimidazole derivatives are effective ROS inhibitors via activating GSH and inhibiting LPO.…”
mentioning
confidence: 99%
“…Recently, compounds 500–501 were reported as promising AChE and BuChE inhibitors (IC 50 = 0.14 and 0.22 μM, respectively), highly neuroprotective against hydrogen peroxide mediated toxicity, metal chelators, and free radical scavengers in the treatment of Alzheimer’s disease ( Sarıkaya et al, 2018 ). Similarly, compounds 502–503 demonstrated duel effects as anti-Alzheimer agents by beta amyloid cleavage enzyme-1 (BACE1) inhibition and neuroprotection ( Gurjar et al, 2020 ). In a 6-hydroxydopamine (6-OHDA)-induced oxidative stress in vitro model assay, compound 504 exerted neuroprotective action compared to melatonin, and reduced superoxide anion radical and hypochlorite level in a luminol-dependent chemiluminescent assay ( Anastassova et al, 2020 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…However, it was observed that BuChE provides a backup to AChE when its activity decreases, and is active at high concentrations of AChE [ 8 ]. Another non-cholinergic role of AchE is the formation of senile plaque by the deposition of beta-amyloid (βA) [ 9 ]. In the beginning, therapeutic strategies for treating diminished cholinergic neurotransmission were mainly focused on AChE inhibitors, but studies have shown the significance of both AChE and BuChE [ 10 ].…”
Section: Introductionmentioning
confidence: 99%